Mesoclimas del Valle del río Colorado y su potencial agropecurario - Burgos, Juan Jacinto (Ecosur, 2025)
A study pf the actual mesoclimatological conditions of the Colorado River Valley from its origin to its mouth in the Atlantic Ocean, has been done, in order to determine the general agricultural conditions of the area, once that the natural enviroments have benn modified by programs of hydrological amelioration now in course. According to the main mesoclimate factores acting on each area, the basic guidelines to achieve the most convenient and rapid adequeteness and stabilization of the modified environment in relation to the appropiate crops and agricultural practices, are given.